Mobilizing media: comparing TV and social media effects on protest mobilization - Boulianne, Shelley; Koc-Michalska, Karolina; Bimber, Bruce (My University, 2020)
The year 2017 saw a cycle of protest ignited by President Trump’s election and subsequent policies. This research seeks to investigate the role of social media and television in raising awareness of protest events and increasing participation in marches and demonstrations. This paper uses data from two surveys conducted in May and June 2017, during the peak of this cycle of protest. We explore the role of social media for protest participation (in general) as well as for awareness and participation in the Women’s March and March for Science. We find that Twitter use offers more consistent effects compared to Facebook in relation to the cycle of protest. In contrast, television use has no impact on awareness and thus, limited potential for mobilization. Social media is distinctive in relation to mobilization, because of social networking features that allow people to learn about specific events, discuss the issues, expose people to invitations to participation, as well as identify members of one’s social network who are also interested in participation.
Keywords: social media; protest; marches; television